Observational study of regional aortic size referenced to body size: production of a cardiovascular magnetic resonance nomogram - Davis, A; Lewandowski, A; Holloway, C; Ntusi, N; Banerjee, R; Nethononda, R; Pitcher, A; Francis, J; Myerson, S; Leeson, C; Donovan, T; Neubauer, S; et al. (BioMed Central, 2014)
Cardiovascular magnetic resonance (CMR) is regarded as the gold standard for clinical assessment of the aorta, but normal dimensions are usually referenced to echocardiographic and computed tomography data and no large CMR normal reference range exists. As a result we aimed to 1) produce a normal CMR reference range of aortic diameters and 2) investigate the relationship between regional aortic size and body surface area (BSA) in a large group of healthy subjects with no vascular risk factors.447 subjects (208 male, aged 19-70 years) without identifiable cardiac risk factors (BMI range 15.7-52.6 kg/m2) underwent CMR at 1.5 T to determine aortic diameter at three levels: the ascending aorta (Ao) and proximal descending aorta (PDA) at the level of the pulmonary artery, and the abdominal aorta (DDA), at a level 12 cm distal to the PDA. In addition, 201 of these subjects had aortic root imaging, allowing for measurements at the level of the aortic valve annulus (AV), aortic sinuses and sinotubular junction (STJ).Normal diameters (mean ±2 SD) were; AV annulus male(♂) 24.4 ± 5.4, female (♀) 21.0 ± 3.6 mm, aortic sinus♂ 32.4 ± 7.7, ♀27.6 ± 5.8 mm, ST-junction ♂25.0 ± 7.4, ♀21.8 ± 5.4 mm, Ao ♂26.7 ± 7.7, ♀25.5 ± 7.4 mm, PDA ♂20.6 ± 5.6, +18.9 ± 4.0 mm, DDA ♂17.6 ± 5.1, ♀16.4 ± 4.0 mm. Aortic root and thoracic aortic diameters increased at all levels measured with BSA. No gender difference was seen in the degree of dilatation with increasing BSA (p>0.5 for all analyses).Across both genders, increasing body size is characterized by a modest degree of aortic dilatation, even in the absence of traditional cardiovascular risk factors.